Self-oscillations in dynamic systems : a new methodology via two-relay controllers /: a new methodology via two-relay controllers. ([2015]) - Aguilar, Luis T; Boĭko, Igorʹ; Fridman, Leonid; Iriarte, Rafael
No abstract available